PENGARUH ALOKASI DANA DESA, PENDAPATAN ASLI DAERAH DAN INDEK PEMBANGUNAN MANUSIA TERHADAP KEMISKINAN KAB/KOTA DI PROVINSI ACEH - Herizal Herizal; Hijri Juliansyah (LPPM Universitas Malikussaleh – Indonesia, 2021)
This study analyzed the effect of Village Fund Allocation, Own-source Revenue, and Human Development Index on Regency/City Poverty in Aceh Province. This study used cross-section data totaling 23 regencies/cities in Aceh Province and time-series data during 2015- 2019. The analysis method used was panel data regression with the help of E-Views 10. The results showed that Village Fund Budget had a value of t- count = 0.699018 < t-table = 1.98157 with an alpha of 0.05. So, it accepted H0 and rejected H1, which indicated that Village Fund Budget had no significant effect on poverty. It can be seen from the probability (p-value) of 0.4860 > 0.05. Own-source Revenue had a value of t-count = 0.018377 < t-table = 1.98157 with an alpha of 0.05. So, It accepted H0 and rejected H2, which indicated that Own-source Revenue had no significant effect on poverty. It can be seen from the probability (p-value) of 0.9854 > 0.05. Human Development Index had a value of t count = -8.727093 > t-table = 1.98157 with an alpha ofSo, it accepted H3 rejected H0, which revealed that the Human Development Index had a significant effect on poverty. It can be seen from the probability (p-value) of 0.0000 < 0.05